Factors That Influence of Family Planning Acceptors in The Selection of IUD Contraceptive Device at The Working Area of Public Health Center in Kemiling Bandar Lampung - Yunitasari, Eva; Boa, Grasiana Florida; Suswanto, Didi (Universitas Aisyah Pringsewu, 2022)
The program launched by the government to suppress the high rate of population growth is the Family Planning program. Nonhormonal contraceptives such as the IUD used by the user are more effective in reducing the failure rate than hormonal contraceptives such as pills, injections, implants. Users of IUD acceptors at the Public Health Center in Kemiling 2022 were IUD 7.78%, MOP (Medical Surgery for Men) 24 11.05%, MOW (Medical Surgery for Women) 26.26%, Implant 44.70%, Injection 86.34%, pill 13.26% and condom 0.03%. The objective of the research was to determine the factors that influence of family planning acceptors in the selection of IUD contraceptive device at the working area of Public Health Center in Kemiling Bandar Lampung 2022. This research type was quantitative research with a cross-sectional approach. The sample in this research were all 151 active family planning participants. The objects in this research were the selection of contraceptives, knowledge, family support, the role of health care workers, and economic status. This research was carried out on December 2021 at the working area of Public Health Center of Kemiling Bandar Lampung. Collecting data with questionnaire sheets, data analysis used univariate and bivariate used Chi-Square. The results showed that there was correlation between knowledge (p-value = 0.041), husband's support (p-value = 0.010), economic status (p-value = 0.020) with the selection of IUD contraceptive devices at the public health center in Kemiling Bandar Lampung 2022, and there is no correlation between the role of health care workers and the selection of IUD contraceptive device at the working area of public health center in Kemiling Bandar Lampung 2022 (p-value = 1,000). It is planned that the public health facility will be able to offer workshops for women of reproductive age, such as contraceptive counseling activities, contraceptive use counseling, and monthly direct contraceptive services. Abstrack: Program yang dicanangkan pemerintah untuk menekan tingginya laju pertumbuhan penduduk yaitu dengan program Keluarga Berencana (KB). Kontrasepsi nonhormonal seperti IUD yang digunakan oleh pemakai lebih efektif menekan tingkat kegagalan dibandingkan alat kontrasepsi hormonal seperti pil, suntik, susuk. Pengguna akseptor IUD di Puskesmas Kemiling tahun 2022 yaitu KB IUD 7.78%, KB MOP: 24 11.05%, KB MOW 26.26%, KB Implant 44.70%, KB Suntik 86.34%, KB pil 13.26% dan KB kondom 0.03%. Tujuan penelitian ini adalah diketahui faktor-faktor yang mempengaruhi Akseptor KB dalam pemilihan alat kontrasepsi IUD di Wilayah Kerja Puskesmas Kemiling Bandar Lampung tahun 2022. Jenis penelitian kuantitatif dengan pendekatan Cross-Sectional. Sampel dalam penelitian ini adalah seluruh peserta KB aktif sebanyak 151. Objek dalam penelitian ini adalah pemilihan alat kontrasepsi, pengetahuan, dukungan keluarga, peran petugas, dan status ekonomi. Penelitian ini telah dilaksanakan pada bulan Desember 2021 di wilayah kerja Puskesmas Kemiling Bandar Lampung. Pengumpulan data dengan lembar kuesioner, analisis data secara univariate dan bivariat (Chi-Square). Hasil penelitian ada hubungan pengetahuan (p-value=0,041), dukungan suami (p-value = 0,010), status ekonomi (p-value = 0,020) dengan pemilihan alat kontrasepsi IUD di Wilayah Kerja Puskesmas Kemiling Bandar Lampung Tahun 2022, dan Tidak ada hubungan peran petugas kesehatan dengan pemilihan alat kontrasepsi IUD di Wilayah Kerja Puskesmas Kemiling Bandar Lampung Tahun 2022 (p-value= 1.000). Diharapkan puskesmas dapat membuka kelas bagi WUS, seperti: kegiatan penyuluhan kontrasepsi, konseling penggunaan kontrasepsi dan pelayanan kontrasepsi langsung yang dilakukan rutin setiap bulan.